Draft Annual Plan 1987-88 Volume I Union Territory of Chandigarh - Planning Commission (Planning Commission, 1987)
Chandigarh is small Union Territory without legislature, and is spread over an area of 114 Sq. K.M., comprising the city of Chandigarh, Manimajra Notified Area Committee and 22 villages. The present population of this Union Territory is approximately 5 lakhs and is likely to go upto about 7.50 lakhs by 1990. The small rural belt is gradually diminishing further with the acquisition of more land for the expansion of the city. Since Chandigarh was never conceived as an Industrial Town, no major industry could be set up here. However, a number of village and small industries have come up during the past years.
Planning & Evaluation Organisation, Finance Department, Chandigarh Administration